Ensembles to Detect Fake News – An Approach Based on Specialized Classifiers - dos Santos, Patrick Antunes; Freire, Paulo Márcio Souza; Goldschmidt, Ronaldo Ribeiro (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2023)
The growing spread of Fake News is a consequence of the popularization of digital media as tools that facilitate the propagation and consumption of information. Ensemble-based approaches to detect this harmful type of news have shown promising performance. Despite their ability to combine machine learning classifiers to achieve more robust results, so far, these approaches have been limited to traditional classifiers (i.e., classifiers that can be applied to problems other than Fake News detection, such as decision trees, K-NN, SVM, etc...). Hence, the present work proposes Ensembles that use, in addition to the traditional ones, classifiers specifically designed to detect Fake News. Preliminary experiments with two datasets showed evidence that the proposed Ensembles have the potential to overcome those that exclusively use traditional classifiers.